2022
DOI: 10.1038/s41598-022-14883-7
|View full text |Cite
|
Sign up to set email alerts
|

Sink survey to investigate multidrug resistance pattern of common foodborne bacteria from wholesale chicken markets in Dhaka city of Bangladesh

Abstract: Antimicrobial resistance (AMR) among foodborne bacteria is a well-known public health problem. A sink survey was conducted to determine the AMR pattern of common foodborne bacteria in cloacal swab of broiler chickens and sewage samples from five wholesale chicken markets of Dhaka city in Bangladesh. Bacteria were identified by culture-based and molecular methods, and subjected to antimicrobial susceptibility testing. Resistance genes were identified by multiplex PCR and sequencing. Multidrug resistance (MDR) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…In case of cefotaxime, this study found 5% and 7% resistance in fecal and environmental isolates, respectively, whereas high resistance has been reported in isolates from poultry cloacal swabs and farm sewage samples in Bangladesh, though in a different region and using a different susceptibility testing protocol [ 22 ]. In this study, E. coli isolates obtained from both fecal and environmental samples were 100% wild type for meropenem, though other studies showed meropenem resistance in cloacal samples, sewerage and hand washes samples in Bangladesh [ 22 , 23 , 35 ]. Considering the fact that meropenem is probably not used in poultry in Bangladesh, the rare occasion of isolating meropenem-resistant E. coli in poultry, likely indicates human to poultry transmission of such isolates.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In case of cefotaxime, this study found 5% and 7% resistance in fecal and environmental isolates, respectively, whereas high resistance has been reported in isolates from poultry cloacal swabs and farm sewage samples in Bangladesh, though in a different region and using a different susceptibility testing protocol [ 22 ]. In this study, E. coli isolates obtained from both fecal and environmental samples were 100% wild type for meropenem, though other studies showed meropenem resistance in cloacal samples, sewerage and hand washes samples in Bangladesh [ 22 , 23 , 35 ]. Considering the fact that meropenem is probably not used in poultry in Bangladesh, the rare occasion of isolating meropenem-resistant E. coli in poultry, likely indicates human to poultry transmission of such isolates.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, E. coli isolates demonstrated high levels of acquired resistance (98% and 89% in fecal and environmental isolates, respectively) to the quinolone-class antibiotic ciprofloxacin [ 36 ]. Ciprofloxacin has been widely used in commercial poultry farms in Bangladesh over the last decade [ 33 , 35 ] though its use in poultry is strictly regulated in the European Union (EU) or even forbidden in the USA and in large parts of the world [ 37 , 38 ]. According to a recent study in Bangladesh, fluoroquinolones were the most frequently used antimicrobial class in broiler chickens [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparable research performed in Bogor Regency, Indonesia, 28% of S. aureus was retrieved from broiler chicken cloacal swabs and 50% was isolated from layer chicken cloacal swabs [16]. Our outcome was lower than those obtained from cloacal swabs of birds sold at five wholesale chicken outlets in Dhaka, Bangladesh (72%) and a broiler farm in Duhok, Iraq (80%) [17,18]. The divergence between our observations and those of Ethiopia might be due to variations in biosecurity or sanitation methods on each chicken farm [19].…”
Section: Introductionmentioning
confidence: 53%
“…In conflict-torn places, collecting samples from the environment can have significant advantages, especially when access to human patients is limited. Environmental samples, such as chicken manure, can provide important information about the presence of foodborne pathogens and AMR, as these pathogens often persist in the environment long after the animals have left ( 20 ).…”
Section: Resultsmentioning
confidence: 99%